Safety Risk Management of Prefabricated Building Construction Based on Ontology Technology in the BIM Environment - Ye Shen; Min Xu; Yini Lin; Caiyun Cui; Xiaobo Shi; Yong Liu (Buildings, 2022)
The extensive application of building information modeling (BIM) technology has brought opportunities and challenges to safety risk management in the field of prefabricated building construction. It is of great significance to provide timely information and knowledge for safety risk decisions in prefabricated building construction, and to display this information visually. In response, based on the ontology theory and using the Revit software, in this study we aimed to establish a monitoring system for the construction of prefabricated buildings, which was verified through a practical case. The results revealed that, first, ontology technology can be applied in the Revit software through plug-in integration, and knowledge regarding construction safety risk management in prefabricated building construction can be shared, reused, and accumulated using this system. Second, problems with the design and construction models of prefabricated buildings that do not meet the specification requirements can be detected by the monitoring system in the Revit software. Third, automatic risk identification and response methods using ontology theory and BIM technologies can effectively promote construction safety risk management performance in relation to prefabricated buildings. These findings examine the application of ontology to the field of prefabricated construction safety risk management for the first time, enrich the research on ontology technology, and contribute to safety risk management in the construction of prefabricated buildings.